Teaching in Orthopaedic Surgery: Effective Strategies for Educating the Modern Learner in a Modern Surgical Practice. Issue 3 (18th July 2022) - Koo, Alexander; Almeida, Bryan Aristega; Kerluku, Jona; Yang, Brian; Fufa, Duretti
Abstract: Prioritizing the education of orthopaedic surgery residents and fellows is essential for the future of the field. This review highlights strategies that educators may find useful in improving their teaching skills for the modern orthopaedic surgery learner. Educators may benefit from focusing on active, effortful, and repetitive engagement in lecture; setting clear expectations to help track progress in clinic; and breaking skills into smaller steps in context of a framework when teaching procedural skills. Providing objective assessment and growth-oriented feedback helps establish a close rapport between educator and trainee while encouraging personal development. Through a remediation process that examines deficiency in core areas and equitability of the learning environment, the trainee and the educator may engage in a fair discussion that prevents trainees from falling behind. Finally, in the era of COVID-19, e-learning and virtual simulations have become increasingly used as effective modalities for teaching clinical knowledge and procedures to trainees. The medical education landscape has been changing at a rapid pace, and by evaluating and adapting to the novel educational models of today, the modern orthopaedic surgeon ensures a learning environment that is equitable, effective, and inspiring for the orthopaedic surgeon of tomorrow.